2021
DOI: 10.1007/jhep07(2021)011
|View full text |Cite
|
Sign up to set email alerts
|

Complexity growth in integrable and chaotic models

Abstract: We use the SYK family of models with N Majorana fermions to study the complexity of time evolution, formulated as the shortest geodesic length on the unitary group manifold between the identity and the time evolution operator, in free, integrable, and chaotic systems. Initially, the shortest geodesic follows the time evolution trajectory, and hence complexity grows linearly in time. We study how this linear growth is eventually truncated by the appearance and accumulation of conjugate points, which signal the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(91 citation statements)
references
References 71 publications
0
91
0
Order By: Relevance
“…A number of works have suggested that certain measures of quantum complexity may have a semiclassical bulk dual [5,12,39,40]. Notions of state complexity [41][42][43][44][45][46][47][48][49] or unitary complexity of time evolution [1,[50][51][52][53][54][55][56] have been intriguingly linked to measures of "size" of the bulk universe at the given boundary time, e.g. the volume of the bulk maximal volume slice [12,31,57] anchored at that time, or the gravitational action in the corresponding Wheeler-de Witt diamond [40].…”
Section: K-complexity and The Black Hole Interiormentioning
confidence: 99%
“…A number of works have suggested that certain measures of quantum complexity may have a semiclassical bulk dual [5,12,39,40]. Notions of state complexity [41][42][43][44][45][46][47][48][49] or unitary complexity of time evolution [1,[50][51][52][53][54][55][56] have been intriguingly linked to measures of "size" of the bulk universe at the given boundary time, e.g. the volume of the bulk maximal volume slice [12,31,57] anchored at that time, or the gravitational action in the corresponding Wheeler-de Witt diamond [40].…”
Section: K-complexity and The Black Hole Interiormentioning
confidence: 99%
“…An interesting approach based on the Euler-Arnold formalism to study complexity in chaotic quantum systems was developed in[149,150].…”
mentioning
confidence: 99%
“…We should finally point out again that we did not aim at writing a comprehensive review of the subject, therefore we left out many topics that we felt were too advanced for an introduction, such as the thermodynamics and resource theory aspects of complexity [43,46,151,152], the relation with bulk dynamics (in the sense of reconstructing the Einstein equations in the bulk from the complexity of the boundary) [85], alternative conjectures, most notably the one in [92] (sometimes called CV 2.0), complexity in de Sitter space [52,[153][154][155], the evolution of complexity after a quench [77,156], the relation between complexity and chaos [32,157], other notions of complexity such as the operator complexity [158,159]. We hope that our readers will be encouraged to delve further into this fascinating subject and contribute to its development.…”
Section: Discussionmentioning
confidence: 99%